Sense of psychological ownership in co‐design processes: A case study - Anette Juel; Lene L. Berring; Annette Erlangsen; Erik R. Larsen; Niels Buus (Wiley, 2024)
Abstract Introduction Service users are increasingly participating in health research. Although collaborative research is assumed to give users a sense of psychological ownership, little is known about the specific psychosocial processes through which ownership develops and is displayed. The present study yields insight into a process in which service users, researchers and a website designer collaborated to design a website. Aim The aim of this study was to explore how participants developed and displayed feelings of ownership during a collaborative process to design a website. Methods A case study design was adopted by which audio recordings were subjected to thematic analysis and interpreted by drawing on the concept of psychological ownership. Findings A sense of psychological ownership of the website design process emerged in two distinct and overlapping phases. In the first phase, 'sense of ownership during the early design phase', only researchers and the website designer displayed a sense of ownership, which was facilitated by the research context preceding the collaborative workshops. In the second phase, 'sense of ownership during the collaborative design phase', service users gradually started to develop parallel feelings of ownership that were facilitated by workshop design activities. These activities enabled service users to increasingly control the process, to invest themselves in the process and to gain intimate knowledge of the process and its outcome. Service users' sense of ownership was displayed in their statements about the website and its elements. Conclusion Participants engaged in codesign processes may develop a sense of psychological ownership at different speeds because of contextual factors. It is important to take this into account as it may complicate the formation of egalitarian work groups. Patient and Public Contribution Parents of children with suicidal behaviour and a counsellor participated as service users in a website design process.